KELEMAHAN YURIDIS FORMAL PELAKSANAAN PERSIDANGAN PIDANA MELALUI TELECONFERENCE SAAT PANDEMI COVID-19 - Wirya Darma, I Made (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2021)
AbstractThe implementation of virtual trials through teleconference is seen as in line with social distancing and physical distancing policies, in order to reduce the pace of development of the Covid-19 Pandemic. As a quick response to the Supreme Court in ensuring the protection of judicial officials, justice seekers, court users including defendants who are dealing with the law, the Supreme Court has issued Supreme Court Circular (SEMA) Number 1 of 2020 concerning Guidelines for Implementing Tasks During the Prevention Period of the Spread of Covid-19 in The environment of the Supreme Court and the Judiciary Bodies that are under it. Within the prosecutor's office, the trial using this teleconference facility refers to the Instruction of the Attorney General of the Republic of Indonesia Number 5 of 2020 concerning Policies for Implementing Tasks and Handling Cases During the Prevention Period for the Spread of COVID-19 in the Public Prosecutor's Office of the Republic of Indonesia on March 27, 2020. Referring to the judicial system criminal law in Indonesia, online court proceedings are a legal breakthrough (rules breaking) in a positive sense. However, in practice the implementation of online trials still encounters obstacles or obstacles.Keywords: online trial; teleconference criminal hearing; virtual courtAbstrakPelaksanaan persidangan virtual melalui sarana teleconference dipandang seiring dengan kebijakan social distancing dan phisyical distancing, guna menekan laju perkembangan Pandemi Covid-19. Sebagai respons cepat Mahkamah Agung dalam menjamin terlindunginya aparatur peradilan, pencari keadilan, pengguna pengadilan termasuk terdakwa yang sedang berhadapan dengan hukum, maka MA telah mengeluarkan Surat Edaran Mahkamah Agung (SEMA) Nomor 1 Tahun 2020 tentang Pedoman Pelaksanaan Tugas Selama Masa Pencegahan Penyebaran Covid-19 di Lingkungan Mahkamah Agung dan Badan Peradilan yang Berada Di Bawahnya. Di lingkungan kejaksaan, persidangan dengan menggunakan sarana teleconference ini merujuk pada Instruksi Jaksa Agung Republik Indonesia Nomor 5 Tahun 2020 tentang Kebijakan Pelaksanaan Tugas dan Penanganan Perkara Selama Masa Pencegahan Penyebaran COVID-19 di Lingkungan Kejaksaan Republik Indonesia pada tanggal 27 Maret 2020. Merujuk kepada sistem peradilan pidana di Indonesia, pelaksanaan sidang secara online merupakan terobosan hukum (rules breaking) dalam makna yang positif. Namun, dalam praktiknya pelaksanaan persidangan online masih menemui kendala atau hambatan.